2012
DOI: 10.1016/j.gloplacha.2011.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Palaeolimnological evidence for an east–west climate see-saw in the Mediterranean since AD 900

Abstract: During the period of instrumental records, the North Atlantic Oscillation (NAO) has strongly influenced interannual precipitation variations in the western Mediterranean, while some eastern parts of the basin have shown an anti-phase relationship in precipitation and atmospheric pressure. Here we explore how the NAO and other atmospheric circulation modes operated over the longer timescales of the Medieval Climate Anomaly (MCA) and Little Ice Age (LIA). High-resolution palaeolimnological evidence from opposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
162
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(193 citation statements)
references
References 85 publications
(103 reference statements)
14
162
3
4
Order By: Relevance
“…A role of the Siberian High (SH), which is responsible for severe cold and dry winter conditions and polar/continental air outbreaks over the Aegean Sea (Rohling et al, 2002), is instead invoked to explain the evidence of 8.2 event in Tenaghi Philippon record ) and centennial-scale SST cooling events in the Aegean Sea (Marino et al, 2009). Finally, comparison of palaeolimnological records from Eastern and Western Mediterranean has highlighted that NAO forcing alone cannot explain the hydrology pattern in Eastern Mediterranean since 900 AD (Roberts et al, 2012). In order to precisely establish the correlation between these two climate systems (SH/NAO) during the late-glacial and Holocene, it is necessary to make a comparison of our data with high-resolution pollen sequences from areas not affected by the SH (i.e.…”
Section: Valsecchi Et Al: Vegetation Dynamics In the Northeasternmentioning
confidence: 99%
“…A role of the Siberian High (SH), which is responsible for severe cold and dry winter conditions and polar/continental air outbreaks over the Aegean Sea (Rohling et al, 2002), is instead invoked to explain the evidence of 8.2 event in Tenaghi Philippon record ) and centennial-scale SST cooling events in the Aegean Sea (Marino et al, 2009). Finally, comparison of palaeolimnological records from Eastern and Western Mediterranean has highlighted that NAO forcing alone cannot explain the hydrology pattern in Eastern Mediterranean since 900 AD (Roberts et al, 2012). In order to precisely establish the correlation between these two climate systems (SH/NAO) during the late-glacial and Holocene, it is necessary to make a comparison of our data with high-resolution pollen sequences from areas not affected by the SH (i.e.…”
Section: Valsecchi Et Al: Vegetation Dynamics In the Northeasternmentioning
confidence: 99%
“…In contrast, isotope records from western Mediterranean lakes do not show such a pattern, suggesting a possible NW-SE bipolar contrast in climate history across the Mediterranean during the Holocene. In more recent syntheses of the mid-Holocene climatic transition in the Mediterranean, Roberts et al (2011Roberts et al ( , 2012 observed that both model output and proxy data suggest an east-west division in the Mediterranean climate history. Regarding the western Mediterranean, they also noted that early Holocene changes in precipitation were smaller in magnitude and less coherent spatially, and that rainfall reached a maximum during the mid-Holocene, around 6000-3000 cal BP, before declining to present-day values.…”
Section: Introductionmentioning
confidence: 99%
“…The sites differ in age, with those on the mainland all being late medieval (thirteenth/fourteenth to sixteenth centuries) while the Balearic sites are earlier (tenth to thirteenth centuries). The decrease in rainfall in the western Mediterranean during the Medieval Climatic Anomaly might be expected to favour millet and sorghum, both drought resistant and with short growing seasons, but this event dates to the eleventh to thirteenth centuries (Roberts et al 2012), and so largely overlaps both the mainland and insular sites.…”
mentioning
confidence: 99%